1999
DOI: 10.1074/jbc.274.14.9707
|View full text |Cite
|
Sign up to set email alerts
|

Rhinovirus Infection Induces Expression of Its Own Receptor Intercellular Adhesion Molecule 1 (ICAM-1) via Increased NF-κB-mediated Transcription

Abstract: Virus infections, the majority of which are rhinovirus infections, are the major cause of asthma exacerbations. Treatment is unsatisfactory, and the pathogenesis unclear. Lower airway lymphocyte and eosinophil recruitment and activation are strongly implicated, but the mechanisms regulating these processes are unknown. Intercellular adhesion molecule-1 (ICAM-1) has a central role in inflammatory cell recruitment to the airways in asthma and is the cellular receptor for 90% of rhinoviruses. We hypothesized that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
318
0
9

Year Published

2000
2000
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 318 publications
(349 citation statements)
references
References 43 publications
(41 reference statements)
21
318
0
9
Order By: Relevance
“…We further demonstrated that influenza A virus induces nuclear translocation of NF-jB and a marked increase in the expression of Mig, IP-10 and I-TAC genes whose promoters contain NF-jB regulatory elements [53][54][55], indicating that the transcription of Mig, IP-10 and I-TAC genes is regulated by NF-jB. The IRF-1 and ICAM-1 promoters contain both a Gas sequence and an NF-jB binding motif [56,57]. Therefore, the influenza-induction of IRF- , and then infected with the original virus (at a 10 -3 dilution) in 1 mL serumfree MEM containing 0.3% BSA and antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…We further demonstrated that influenza A virus induces nuclear translocation of NF-jB and a marked increase in the expression of Mig, IP-10 and I-TAC genes whose promoters contain NF-jB regulatory elements [53][54][55], indicating that the transcription of Mig, IP-10 and I-TAC genes is regulated by NF-jB. The IRF-1 and ICAM-1 promoters contain both a Gas sequence and an NF-jB binding motif [56,57]. Therefore, the influenza-induction of IRF- , and then infected with the original virus (at a 10 -3 dilution) in 1 mL serumfree MEM containing 0.3% BSA and antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…High intakes of vitamin C have been associated with the treatment of viral infections, most notably the common cold and HIV-1. Rhinovirus is reliant on NF-B-dependent processes both for cell invasion and for the pathogenesis of infection (58,59). As regards HIV-1, clinical improvement was claimed in AIDS patients who ingested high doses of vitamin C (9), and it has been shown to suppress HIV-1 replication in chronically and acutely infected cells (60,61).…”
Section: Discussionmentioning
confidence: 99%
“…4 Lipopolysaccharide, respiratory syncytial virus and rhinovirus are known to increase NF-kB-mediated transcription of the ICAM-1 gene in A549 cells. [5][6][7] Recombinant adenoviral vectors have been shown to activate NF-kB in murine hepatocytes, murine dendritic cells and human vascular smooth muscle cells. [8][9][10] These reports suggested a role for NFkB in the transcriptional regulation of ICAM-1 gene induced by Ad.CFTR.…”
Section: Moter Adcftr Also Stimulated a 13-fold Increase In Nfkb-dementioning
confidence: 99%